The magic gifts - Punter, Russell; Bernstein, Gabo (Usborne London, 2009)
Cheated out of a fortune, Chin's luck changes when he meets a mysterious monk. For the old man's gifts of a mat, a spoon and a pair of chopsticks are not as ordinary as they seem. The classic Korean folktale retold with easy-reading text for children who have just started reading alone.